Development of Fastnet config application / Ahmad Harisan Muhamad - Muhamad, Ahmad Harisan (Faculty of Computer and Mathematical Sciences, 2007)
Nowadays, the usage of computer and network technology seems to be necessity for the most work environments. This technology become important since it provides users with an access to the data resources and internet. Besides providing data access, data can also be shared. In order to stay connected to the network, users need to make some setting of network configuration on their computers. The main objective of this research is to develop an application which can store multiple network configurations as profiles and activate the profiles in the future. This project will be focused on the development of an application which can store multiple configuration of network as profiles. These profiles will be stored in separate storing location for retrieval later. The scope of the application is to cater for wired network. Finally, the contribution of the project is it will provide effectiveness in term of time, means that users can activate a particular network configuration profile, without any reconfiguration. What they have to do is activate the profile at system startup. This application will automatically sets the IP address, Subnet Mask, Default Gateway and DNS for NIC and also changes the Internet Explorer Proxy Setting accordingly to the applied profile.